(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In this article Factors affecting the formation of students-young people’s ability to understand historical reality and explain it logically, development of historical thinking, maturation as a mature person with intellectual potential through pedagogical and psychological means of growing students as professionals development is covered.